The Changing Governance of Higher Education and Research: Multilevel Perspectives - Jansen, Dorothea (Springer, 2016)
This book analyses and describes the effects of the reforms of the European science systems on research. Taking the multilevel governance of the science system into account, the authors describe the effects of the reforms on different aspects: research collaborations and research lines, PhD education, performance profiles, research funding and legal aspects. The first part of the book deals with “PhD education” from an economic perspective. How successful are Research Training Groups and is heterogeneity really a factor of success? What kind of PhD education leads to success? The second part focuses on the interactions of governance and research. How do changes at the national and organisational level influence research cooperation, research lines and research performance? The third part reflects the Europeanisation and Internationalisation of research and research funding. To what extent are research collaborations becoming international? How is the role of European funding agencies changing?